CULTURE OF WESTERN AND EASTERN COUNTRIES: NATIONAL HOLIDAYS, TRADITIONS, AND CUSTOMS (Modern education and development, 2025)
This article aims to study the national traditions and customs of Western and Eastern countries, their culture, their differences and their common aspects.